Regeneration of a distinctive set of axosomatic contacts in the leech central nervous system - French, KA (J Neurosci, 1986)
The nociceptive sensory neurons (N cells) in the leech Hirudo medicinalis contact other neurons through conventional synapses in the neuropile and through baskets of processes that wrap the somata of particular cells. These axosomatic contacts are made with the pressure (P) and N sensory neurons in the adjacent segmental ganglia, but not with cells within the same ganglion as the wrapping cell. Physiological evidence indicates that these contacts may be synaptic, although conventional synapses have not been observed with electron microscopy. After they have been injured, lateral N cell processes can grow into the anterior adjacent ganglion and regenerate somatic contacts. In general, regenerated N cell processes wrap the same somata as do intact N cells, but they often wrap fewer somata. However, six of 14 regenerated N cells also wrapped the soma of a small posterior cell that was contacted in only one of 120 normal ganglia examined. It thus appears that the growing processes of an injured N cell select certain cell somata to wrap, but that the selection is somewhat broader than that in the embryonic leech.